Effect of Washing on the Adhesion of Yersinia enterocolitica on Fish and Shrimp Muscle Surface - Kishore, Pankaj; Suma, D; Minimol, V A; Thakur, Abhishek; Uchoi, Devananda; Nayak, B B (Fishery Technology, 2017)
Water is used traditionally with or without a sanitizing agent to wash fresh seafood and to reduce pathogens attached to the surface. Ability of Yersinia enterocolitica to get attached to fish and shrimp muscle and detached during water washing was studied. Dressed tissues were dipped in suspension containing Yersinia enterocolitica 108-109 cells per ml and washed sequentially. Bacterial counts and tetrazolium salt reduction were estimated. The study revealed that first wash was more effective compared to two subsequent washes. The bacterial reduced from 5.145 log CFU g-1 to 4.445 log CFU g-1 in fish and 5.05 to 3.7 log CFU g-1 in shrimp after 3 washings. The cells which remained bound after washing were more active than those which got washed and were measured by per cell activity of the cells monitored by rate of formazan formed. The washing was found to be more effective in removing bacteria in shrimp tissue than in fish tissue provided initial quality of water was good.